Efektivitas Pupuk Kotoran Sapi dan Pemacu Pertumbuhan Akar Bambu terhadap Hasil Tanaman Terung Ungu (Solanum melongena L.) - Jihan Nabila; Andi Apriany Fatmawaty; Kiki Roidelindho; Susiyanti Susiyanti (Jurnal Ilmiah Membangun Desa dan Pertanian, 2025)
This research aims to analyze the results of administering doses of cow dung fertilizer and concentrations of plant growth promoters from bamboo roots on the yield of purple eggplant (Solanum melongena L.). Proper fertilization plays an important role in increasing eggplant production, but too much inorganic fertilizer can degrade soil fertility and pollute the environment. Organic fertilizers and biofertilizers (such as PGPR) offer a sustainable solution with less environmental impact. This research occurred in the Banten Agricultural Instrument Standards Center area and was carried out from September 2024 to December 2024. This research used factorial RAK. Cow animal manure (S) is the first factor with three levels, namely S1 400g/polybag, S2 500g/polybag, S3 600g/polybag, and the second factor is plant growth promoter /PGPR (P) from bamboo roots with four levels, namely P0 0ml/l, P1 20ml/l, P230 ml/l, P3 40 ml/l. Each treatment was repeated three times, resulting in 36 treatment combinations. If a difference is found after a variance analysis at the 5% level, a DMRT is performed at the 5% level. The variables observed were plant height, number of leaves, number of fruit, fruit weight per plant, fruit per plant, fruit length, and fruit diameter. The research results showed that applying 400 g/polybag of cow dung fertilizer had the best impact on plant height parameters of 8.15 cm and the number of leaves of 6.83 at the age of 2 MSPT. Plant growth promoter from bamboo roots with a concentration of 40 ml/l gave the best effect on fruit number 5.00, length 14.79 cm, and weight 419.42 grams.